Transoral Mucosal Excision Sutured Gastroplasty: A Pilot Study for GERD and Obesity With Two-Year Follow-Up. (October 2014) - Legner, Andras; Altorjay, Aron; Juhasz, Arpad; Stadlhuber, Rudolph; Reich, Viktor; Hunt, Brandon; Rothstein, Richard; Filipi, Charles
Introduction . An outpatient transoral endoscopic procedure for gastroesophageal reflux disease (GERD) and obesity would be appealing if safe, effective, and durable. We present the first in human experience with a new system. Methods . Eight patients with GERD (3) and obesity (5) were selected according to a preapproved study protocol. All GERD patients had preprocedure manometry and pH monitoring to document GERD as well as quality of life and symptom questionnaires. Obese patients (body mass index >35) underwent a psychological evaluation and tests for comorbidities. Under general anesthesia, a procedure was performed at the gastroesophageal junction including mucosal excision, suturing of the excision beds for apposition, and suture knotting. Results . One patient with micrognathia could not undergo the required preprocedural passage of a 60 F dilator and was excluded. The first 2 GERD patients had incomplete procedures due to instrument malfunction. The subsequent 5 subjects had a successfully completed procedure. Four patients were treated for obesity and had an average excess weight loss of 30.3% at 2-year follow-up. Of these patients, one had an 8-mm outlet at the end of the procedure recognized on video review—a correctable error—and another vomited multiple times postoperatively and loosened the gastroplasty sutures. The treated GERD patient had resolution of reflux-related symptoms and is off all antisecretory medications at 2-year follow-up. Her DeMeester score was 8.9 at 24 months. Conclusion . The initial human clinical experience showed promising results for effective and safe GERD and obesity therapy.